Water markets in the Fordwah/Eastern Sadiqia area: an answer to perceived deficiencies in canal water supplies? - Strosser, P.; Kuper, M. (International Irrigation Management Institute, 1994)
This paper presents the results of a study on water markets in the Fordwah/Eastern Sadiqia Area, Punjab, Pakistan. The study stresses and quantifies the importance of water markets in the area. A first attempt is made to evaluate the the impact of water marketson the quality of irrigation services.